THE PERCEPTION OF SECURITY AND RISK, EASE OF USE, AND BENEFITS ARE THE DETERMINING FACTORS IN ADOPTING A DIGITAL WALLET - Karsim, Karsim; Rini, Rini; Ronaldo, Reza; Anam, Syaiful; Judijanto, Loso (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The COVID-19 era is an event that transitions all human activities in all parts of the world. This has an impact on various aspects including health, economic, and social aspects. All activities are carried out indoors and limit contact outside the room to avoid COVID-19, from social distancing to working from home. The implementation of this system makes people more 'literate' in technology. One of them is in the economic sector, where people have started using non-cash payment transactions. Because of this phenomenon, researchers analyzed the perception of security and risk, and benefits as the determining factors of in adopting the digital wallet. This research uses interviews and direct observation. The data collection was carried out on 15 respondents, people who have a high interest in the use of digital wallets. The results show that perceived security, ease of use, and benefits are the main factors in digital wallet adoption. Users prefer platforms with security features such as encryption and two-factor authentication. Perceived risks, such as data loss, can be mitigated with good education. Ease of use through an intuitive interface increases user satisfaction. Benefits such as ease of payment and financial incentives are strong motivators. To increase adoption, providers should focus on security, convenience, and clear communication of benefits. Keywords: Digital Wallet; Security and Risk; Benefits